Analysis of Some Practical Life Uses and Applications of Exponential Function - Pandit, Jay Kumar; Sahani, Suresh Kumar; Sahani, Kameshwar (Darul Yasin Al Sys, 2024)
We have sorted out some practical uses of exponential function that we are going to study in this report. The report is given more emphasis on real life use of Euler number i.e. e and also on the uses of other exponential function. The sorted out uses of exponential function is based on following topic: real value of money, bit coin value, household saving, production in a factory, and exploitation of forest. Later on, we have also focused on consequences of those problems and find its solution. This work is motivated by the work of [1-13].